That Ever Loyal Island : Staten Island and the American Revolution. - Papas, Phillip (NYU Press, 2009)
Of crucial strategic importance to both the British and the Continental Army, Staten Island was, for a good part of the American Revolution, a bastion of Loyalist support. With its military and political significance, Staten Island provides rich terrain for Phillip Papas's illuminating case study of the local dimensions of the Revolutionary War. Papas traces Staten Island's political sympathies not to strong ties with Britain, but instead to local conditions that favored the status quo instead of revolutionary change. With a thriving agricultural economy, stable political structure, and strong.